OXR2 increases plant defense against a hemibiotrophic pathogen via the salicylic acid pathway - Mencia, Regina (2020)
Arabidopsis thaliana OXIDATION RESISTANCE 2 (AtOXR2) is a mitochondrial proteinbelonging to the Oxidation Resistance (OXR) protein family, recently described in plants. Weanalyzed the impact of AtOXR2 in Arabidopsis defense mechanisms against thehemibiotrophic bacterial pathogen Pseudomonas syringae. oxr2 mutant plants are moresusceptible to infection by the pathogen and, conversely, plants over-expressing AtOXR2(oeOXR2 plants) show enhanced disease resistance. Resistance in these plants is accompaniedby higher expression of WRKY transcription factors, induction of genes involved in salicylicacid (SA) synthesis, accumulation of free SA, and overall activation of the SA-signalingpathway. Accordingly, defense phenotypes are dependent on SA-synthesis and SA-perceptionpathways, since they are lost in ics1/sid2 (isochorismate synthase 1/salicylic acid inductiondeficient 2) and npr1 (nonexpressor of pathogenesis-related genes 1) mutant backgrounds.Over-expression of AtOXR2 leads to faster and stronger oxidative burst in response to thebacterial flagellin peptide flg22. Moreover, AtOXR2 affects the nuclear localization of thetranscriptional coactivator NPR1, a master regulator of SA signaling. oeOXR2 plants haveincreased levels of total glutathione and a more oxidized cytosolic redox cellular environmentunder normal growth conditions. Therefore, AtOXR2 contributes to establishing plantprotection against infection by P. syringae acting on the activity of the SA pathway.